Tanggung Jawab Hukum Pelaku Usaha Atas Peredaran Kosmetika Yang Diduga Mengandung Bahan Berbahaya Dan Tidak Memenuhi Standart Mutu Menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Kosumen (Studi Kasus Produk Kosmetika Hasil Rilis BPOM) - Dede Afandi Hamid; Ermanto Fahamsyah (Jurnal Hukum Adigama, 2019)
UUPK has explained that the legal instrument which protect the consumers was not intended to shut off the business of businessmen. But actually it becomes a Healthy Business Season and becomes a strong company in facing up the rivalry through the supply of high quality goods and services.Human was perfectly created by God. The willingness in  every human  to appear more attractive and perfect has become a trend, not only for women but also men as well as teenagers that we are  called “millennials” becomes a proper things.The definition of cosmetic under The Regulation of Ministry of Health 1175/2010 about the cosmetic production permit is the ingredients and preparations to be used on the outside of the human body (epidermis, hair, nails, mouth, and outer genital organs). Head of BPOM appeals to the public to be smart consumers in choosing cosmetics. During 2018, BPOM has foreclosed illegal cosmetics worth 106.9 billion rupiah. In that Case, BPOM asked to the public to avoid some cosmetic products.